Business Scope Mapping Analysis, Study on Business Portfolio of PT JKL - Sumitomo Ueno (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
PT JKL is a company operating in passenger and land transportation services. The company has not conducted a routine business scope mapping analysis, with the last evaluation carried out in 2017. This study aims to analyze each business scope managed by PT JKL and to identify potential synergies among the business units. Business scope mapping is crucial because most of PT JKL’s subsidiaries are highly sensitive to changes in human mobility. Significant factors contributing to the company’s revenue decline include the COVID-19 pandemic and the rapid growth of ride-hailing services. Data was collected through questionnaires and in-depth interviews with key decision makers, including members of the board of directors. The analysis incorporates industry attractiveness, competitive strength of each business scope, and financial performance indicators such as corporate earnings. These variables were mapped using a 9-cell matrix to evaluate the contribution of each business scope and to support the formulation of more comprehensive corporate strategies aimed at maximizing value creation. The results indicate that all business scopes of PT JKL have high investment priority. The auction business also shows high industry attractiveness but has moderate competitive strength and the smallest net revenue contribution during the 2019–2021 period